PELATIHAN IMPLEMENTASI KWL CHART UNTUK MENINGKATKAN KEMAMPUAN MEMBACA TEKS BAHASA INGGRIS KOMPUTER PADA MAHASISWA STMIK KHARISMA MAKASSAR - Adys, Himala Praptami; Usman, Misnawaty; Amin, Fatimah Hidayahni; Sunusi, Seny Luhriyani; Adys, Himaya Praptani (MEDIA INOVASI PENDIDIKAN DAN PUBLIKASI, 2024)
Pelatihan implementasi strategi KWL Chart bertujuan untuk meningkatkan kemampuan membaca teks bahasa Inggris di bidang komputer. Pelatihan ini dilaksanakan di STIMIK Kharisma Makassar deangn pserta pelatihan berjumlah 25 mahasiswa. Tedapat empat sesi pelathan. Pada sesi pertama, mahasiswa dilatih memilih bacaan yang relevan dengan bidangnya dari sumber ilmiah. Sesi kedua difokuskan pada pengenalan konsep KWL Chart yang interaktif. Sesi ketiga, mahasiswa mempresentasikan KWL Chart dan diikuti sesi diskusi. Sesi terakhir berupa wawancara yang mengevaluasi efektivitas KWL Chart dalam aspek kognitif, motivasional, implementasi, dan kemajuan. Hasil pelatihan berdasarkan wawancara menunjukkan bahwa mahasiswa merasa lebih termotivasi, mandiri, dan mampu menghubungkan pengetahuan awal dengan teks yang dibaca, yang secara signifikan meningkatkan kemampuan membaca mereka. Kata Kunci: KWL Chart, Membaca Pemahaman, Teks Bahasa Inggris Komputer Abstract: The Implementation Training of the KWL Chart Strategy Aimed at Enhancing English Text Reading Comprehension in Computer Sciences. This academic intervention was conducted at STIMIK Kharisma Makassar, involving a cohort of 25 undergraduate students. The training program was structured across four comprehensive sessions designed to systematically improve students' academic reading capabilities. In the initial session, participants were systematically guided in selecting scholarly sources and texts most pertinent to their disciplinary domain. The second session was dedicated to an interactive and pedagogically robust introduction to the KWL (Know, Want to Know, Learned) Chart methodology, emphasizing its strategic cognitive scaffolding potential. During the third session, students were required to present their individually constructed KWL Charts, followed by a rigorous scholarly discourse and peer-to-peer analytical discussion. The concluding session comprised a structured interview protocol meticulously evaluating the KWL Chart's effectiveness across multiple dimensions: cognitive engagement, motivational impact, implementation efficacy, and incremental learning progression. Qualitative analysis derived from post-intervention interviews revealed statistical significant attitudinal and performative transformations. Participants reported heightened intrinsic motivation, increased academic autonomy, and an enhanced capacity to systematically integrate prior knowledge with textual content, which collectively contributed to substantive improvements in their English reading comprehension capabilities within the computer sciences discipline. Keywords: KWL Chart, Reading Comprehension. Computer English Text